Common injuries in athletes with obesity and diabetes - Wilder, R. P.; Cicchetti, M. (Clinics in Sports Medicine, 2009)
Musculoskeletal injuries and diseases are common in persons with obesity and diabetes mellitus. High body mass index is associated with an increased risk for musculoskeletal injuries, diseases, and disability. There is a significant positive correlation between the level of obesity and musculoskeletal injuries, and disability and health-related costs. The prevalence of obesity and diabetes is inversely proportional to health-related quality of life.